Spatial-temporal changes of iron deposition and iron metabolism after traumatic brain injury in mice - Cheng, Hao; Wang, Ning; Ma, Xingyu; Wang, Pengfei; Dong, Wenwen; Chen, Ziyuan; Wu, Mingzhe; Wang, Ziwei; Wang, Linlin; Guan, Dawei; Zhao, Rui (Frontiers in Molecular Neuroscience, 2022)
Excessive iron released by hemoglobin and necrotic tissues is the predominant factor that aggravates the outcome of traumatic brain injury (TBI). Regulating the levels of iron and its metabolism is a feasible way to alleviate damage due to TBI. However, the spatial-temporal iron metabolism and iron deposition in neurons and glial cells after TBI remains unclear. In our study, male C57BL/6 mice (8–12 weeks old, weighing 20–26 g) were conducted using controlled cortical impact (CCI) models, combined with treatment of iron chelator deferoxamine (DFO), followed by systematical evaluation on iron deposition, cell-specific expression of iron metabolic proteins and ferroptosis in ipsilateral cortex. Herein, ferroptosis manifest by iron overload and lipid peroxidation was noticed in ipsilateral cortex. Furthermore, iron deposition and cell-specific expression of iron metabolic proteins were observed in the ipsilateral cortical neurons at 1–3 days post-injury. However, iron overload was absent in astrocytes, even though they had intense TBI-induced oxidative stress. In addition, iron accumulation in oligodendrocytes was only observed at 7–14 days post-injury, which was in accordance with the corresponding interval of cellular repair. Microglia play significant roles in iron engulfment and metabolism after TBI, and excessive affects the transformation of M1 and M2 subtypes and activation of microglial cells. Our study revealed that TBI led to ferroptosis in ipsilateral cortex, iron deposition and metabolism exhibited cell-type-specific spatial-temporal changes in neurons and glial cells after TBI. The different effects and dynamic changes in iron deposition and iron metabolism in neurons and glial cells are conducive to providing new insights into the iron-metabolic mechanism and strategies for improving the treatment of TBI.